Development of Vertebral Column in Children and Youths from Lower Silesia - Goździewski, Stanisław; Marek, Janusz; Bujacz, Elżbieta; Szydło, Krystyna (Anthropological Review, 1977)
The authors measured the vertebral column as a whole, its parts, and body height in a group of children and youths from Ząbkowice Śląskie (Silesia), comprising 595 boys and 602 girls. The material was analyzed in yearly age groups from 3 up to 16 years, and cases of definitely abnormal posture were excluded before statistical elaboration. Based on measurements, eight indices were calculated. It was found that the values of these indices vary with sex and age. Absolute and relative rates of growth for spondylometric characters and body height were calculated, and the rhythm of annual increments was observed. It was found that the growth of the parts of the vertebral column is characterized by a considerable variability of rhythm and sexual dimorphism. During adolescence in both sexes, rates of vertebral column growth are distinctly higher than those of body height. All the examined spondylometric characters show velocity peaks. The length of the vertebral column is significantly and positively correlated with body height. The diminished capacity of spinal muscles to be adapted to the rate of the vertebral column may be considered as one of the factors explaining the incidence of kifotic posture among youths.